2013
DOI: 10.1111/1756-185x.12096
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between senescence‐associated beta‐galactosidase expression in articular cartilage and disease severity of patients with knee osteoarthritis

Abstract: SA-beta-Gal expression in articular cartilage is associated with progressive knee OA joint damage and is a potential indictor of disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…Chondrocytes can be isolated and cultured from TKA cartilage tissue. While patient variability exists, in our experience and in the literature, a consistent percentage of senescent chondrocytes are present in OA patient-derived chondrocytes (21,46,49,50). We found that treating these chondrocytes with a small-molecule senolytic reduced SnC burden and upregulated expression and deposition of type II collagen and aggrecan, the two primary ECM components of cartilage (22).…”
Section: Sncs In the Kneementioning
confidence: 58%
See 2 more Smart Citations
“…Chondrocytes can be isolated and cultured from TKA cartilage tissue. While patient variability exists, in our experience and in the literature, a consistent percentage of senescent chondrocytes are present in OA patient-derived chondrocytes (21,46,49,50). We found that treating these chondrocytes with a small-molecule senolytic reduced SnC burden and upregulated expression and deposition of type II collagen and aggrecan, the two primary ECM components of cartilage (22).…”
Section: Sncs In the Kneementioning
confidence: 58%
“…For many years, senescent chondrocytes were noted in cartilage tissue discards from diseased joints after total knee arthroplasty surgery (22,(48)(49)(50). Senescent chondrocytes accumulate with age and are present at higher numbers in human OA cartilage compared with age-matched healthy cartilage (18,21,45,46,(50)(51)(52).…”
Section: Sncs In the Kneementioning
confidence: 99%
See 1 more Smart Citation
“…In knee OA, Gao et al . () demonstrated a correlation between SAβGal expression and disease severity of patients. They investigated the levels of SAβGal expression in normal cartilage compared with OA cartilage of differing severity (mild, moderate, and severe).…”
Section: Senescence In Osteoarthritis Pathologymentioning
confidence: 91%
“…Our results also show that high levels of Cx43 in chondrocytes are related to an increase in senescence associated with a higher expression of p16 INK4a and high levels of p53. Recent studies highlight the importance of senescence in osteoarthritis [29][30][31][32][33] . In fact, Jeon et al published an article in Nature Medicine where they showed senescence as a new therapeutic target to treat osteoarthritis and promote the regeneration of cartilage 33,34 .…”
Section: Originalsmentioning
confidence: 99%